Strategies to foster stakeholder engagement in residency coaching: a CFIR-Informed qualitative study across diverse stakeholder groups - Marzena Sasnal; Rachel M. Jensen; Uyen T. Mai; Carl A. Gold; Aussama K. Nassar; James R. Korndorffer; Arden M. Morris; Rebecca K. Miller-Kuhlmann (Medical Education Online)
Introduction Coaching interventions in graduate medical education have proven successful in increasing technical and communication skills, reducing errors, and improving patient care. Effective stakeholder engagement enhances the relevance, value, and long-term sustainability of interventions, yet specific strategies for stakeholder engagement remain uncertain. The purpose of this article is to identify strategies to foster engagement of diverse stakeholder groups in coaching interventions.Material and Methods We conducted 35 semi-structured interviews between November 2021 and April 2022 with purposively sampled key stakeholders that captured participants’ perspectives on physicians’ communication training needs, roles, and involvement in, as well as contextual factors, facilitators, barriers, and improvement strategies of the multi-departmental Communication Coaching Program at our institution. We utilized the Consolidated Framework of Implementation Research to guide data collection and analysis. An analytic approach relied on team-based thematic analysis with high inter-coder agreement between three raters (Cohen’s kappa coefficient 0.83). Several validation techniques were used to enhance the credibility and trustworthiness of the study.Results Analysis of transcribed interviews with stakeholders directly involved in the Communication Coaching Program, including 10 residents, 10 faculty coaches, 9 medical education leaders, and 8 programmatic sponsors, revealed five key engagement strategies: (1) embrace collaborative design, (2) enable flexible adjustments and modifications, (3) secure funding, (4) identify champions, and (5) demonstrate outcomes. Additionally, a patient-centered approach to delivering the best possible patient care emerged as a primary objective that linked all stakeholder groups.Discussion Evaluating the experiences of key stakeholders in the Communication Coaching Program helped identify targetable strategies to facilitate participant engagement across all organizational levels. The analysis also revealed universal alignment around the importance of providing high-quality patient care. Insights from this work provide guidance for clinical training programs moving toward the implementation of coaching interventions.